Involucrin in the differential diagnosis between linear psoriasis and inflammatory linear verrucous epidermal nevus: a report of one case - Flávia Regina Ferreira; Nilton Gioia Di Chiacchio; Márcia Lanzoni de Alvarenga; Samuel Henrique Mandelbaum (Sociedade Brasileira de Dermatologia, 2013)
Inflammatory linear verrucous epidermal nevus is a variant of verrucous epidermal nevus, characterized by recurrent inflammatory phenomena. Despite well-established clinical manifestations, the differential diagnosis between inflammatory linear verrucous epidermal nevus and linear psoriasis remains difficult. Clinical history, physical examination and histopathology analysis may not be sufficient to confirm the diagnosis. We report the case of a 4-year-old girl in which the involucrin immunostaining was helpful in the diagnosis of inflammatory linear verrucous epidermal nevus. Our findings confirm that involucrin immunohistochemistry is a useful tool in such cases.